First-Pass Effect Predicts Clinical Outcome and Infarct Growth After Thrombectomy for Distal Medium Vessel Occlusions. Issue 6 (17th December 2022) - Farouki, Yousra; Bonnet, Thomas; Mine, Benjamin; Hulscher, Franny; Wang, Maud; Elens, Stephanie; Vazquez Suarez, Juan; Jodaitis, Lise; Ligot, Noémie; Naeije, Gilles; Walker, Gregory; Lubicz, Boris; et al.
Abstract : BACKGROUND: The first-pass effect in endovascular thrombectomy (EVT) has been associated with better clinical outcomes and decreased stroke progression in large vessel occlusion but has not been evaluated in distal, medium vessel occlusions (DMVOs). OBJECTIVE: To assess the impact on clinical outcome and stroke progression of the modified first-pass effect (defined as a successful first-pass [modified Thrombolysis In Cerebral Infarction 2b/2c/3] revascularization) in patients who underwent EVT for a primary DMVOs. METHODS: We collected data from consecutive patients who underwent EVT for a primary DMVO at a single large academic center. We compared the rate of good clinical outcome (modified Rankin Scale of 0-2 at 3 months) and stroke progression between patients who demonstrated modified first-pass effect (mFPE) vs those who did not (no-mFPE). RESULTS: Between January 2018 and January 2021, we included 60 patients who underwent EVT for an acute ischemic stroke with a primary DMVO. Overall, mFPE was achieved in 32% (19/60) of EVTs. The mFPE was associated with a higher rate of good clinical outcome compared with no-mFPE (89% vs 46%, odds ratio = 16.04 [2.23-115.39], P = .006 in multivariate analysis). Final stroke volume was less among mFPE patients (6.9 mL [4.7-13.6] vs 23 mL [14.6-47], P = .001) as was stroke progression (6.8 mL [4-12.1] vs 17.8 mL [8.1-34.9], P = .016). The mFPE was still associated with higher rates of good clinical outcome when compared with patients reaching an modified Thrombolysis In Cerebral Infarction score ≥2b in more than 1 pass (89% vs 53%; odds ratio = 7.37 [1.43-38.08], P = .017). CONCLUSION: The mFPE may be associated with better clinical outcomes and lower stroke progression in DMVO. Abstract :